AN ASSESSMENT OF GROUNDWATER QUALITY FOR THE SUITABILITY OF IRRIGATION IN RELIZANE PLAIN, ALGERIA - B., Mekhloufi1, Benyahia2 M. (university of eloued جامعة الوادي, 2020)
Located in an area characterized by an arid climate, the plain of La Mina, records an annual rainfall of 300 mm and an evapotranspiration equal to 1500 mm, which generates a deficit of 1200 mm, this shortage of water allocated to agriculture, forced farmers to use groundwater. The soils of the plain of the Mina and in particular the soil of the irrigated perimeters, suffer from a problem of salinization. Irrigation methods and the quality of the water used are the decisive triggers. The results of the hydrochemical analyzes carried out, focused on the major elements of these waters. They mainly have a sodium chloride facies, an EC average of (5.16 dS / m) which indicates that the waters are heavily salted, an average value of (SAR) of 20.67, shows that there is a very high risk of sodicity, playing a role in the physical degradation of soils. The Riverside and Wilcox diagrams show that it is the C4S4 class which is the most dominant, corresponding to a water of very high salinity and strongly sodium of poor quality, not recommended for irrigation.
artical
Keywords: Mina Plain, Irrigation Water, Hydrogeology, Salinization.